Agency in physiological dynamics. (22nd June 2022) - Rogers, James; Gallaher, Edward J.; Dingli, David
Abstract: With a view to finding new applications of biomedical system dynamics, this article expands upon on our talk at the 2021 International System Dynamics Conference on the occasion of receiving the J. W. Forrester Award for the article, "Personalized ESA doses for anemia management in hemodialysis patients with end‐stage renal disease" (System Dynamics Review 2018, 34(1–2): 121–153). We summarize the evolution of a project which took place in a clinical setting between 2008 and 2015 that led to the award‐winning article. We present concepts from receptor theory that informed the first system dynamics application of biophysical system dynamics to the successful diagnosis, prescription, administration, and improvement of individualized patient care. We expand upon these ideas to present a generalized structure, DART (Dynamic Approach to Receptor Theory). It can be used to simulate the physiological effects of any agent, be it an exogenous pharmacological agent, an endogenous enzyme or hormone, or a toxin of some sort. We suggest including within the pharmacological technical literature easily acquired but frequently omitted critical parameter values and rate constants. These would enable researchers to perform transient analyses of biophysical phenomena in addition to static equilibrium analyses typically performed. With the availability of this data, we suggest that the fundamental tools of system dynamics might be used to reconceptualize the 100‐year‐old field of "occupation theory" (today, receptor theory) to deliver high‐resolution insights into physiological dynamics and the preventive, prescriptive, and palliative interventions they might require. It is our hope that these ideas could pave the way forward to novel, groundbreaking applications in biomedical system dynamics. © 2022 System Dynamics Society.